Bone Morphogenetic Protein 7 Gene Delivery Improves Cardiac Structure and Function in a Murine Model of Diabetic Cardiomyopathy - Tate, Mitchel; Perera, Nimna; Prakoso, Darnel; Willis, Andrew M.; Deo, Minh; Oseghale, Osezua; Qian, Hongwei; Donner, Daniel G; Kiriazis, Helen; De Blasio, Miles J.; Gregorevic, Paul; Ritchie, Rebecca H. (Frontiers in Pharmacology, 2021)
Diabetes is a major contributor to the increasing burden of heart failure prevalence globally, at least in part due to a disease process termed diabetic cardiomyopathy. Diabetic cardiomyopathy is characterised by cardiac structural changes that are caused by chronic exposure to the diabetic milieu. These structural changes are a major cause of left ventricular (LV) wall stiffness and the development of LV dysfunction. In the current study, we investigated the therapeutic potential of a cardiac-targeted bone morphogenetic protein 7 (BMP7) gene therapy, administered once diastolic dysfunction was present, mimicking the timeframe in which clinical management of the cardiomyopathy would likely be desired. Following 18 weeks of untreated diabetes, mice were administered with a single tail-vein injection of recombinant adeno-associated viral vector (AAV), containing the BMP7 gene, or null vector. Our data demonstrated, after 8 weeks of treatment, that rAAV6-BMP7 treatment exerted beneficial effects on LV functional and structural changes. Importantly, diabetes-induced LV dysfunction was significantly attenuated by a single administration of rAAV6-BMP7. This was associated with a reduction in cardiac fibrosis, cardiomyocyte hypertrophy and cardiomyocyte apoptosis. In conclusion, BMP7 gene therapy limited pathological remodelling in the diabetic heart, conferring an improvement in cardiac function. These findings provide insight for the potential development of treatment strategies urgently needed to delay or reverse LV pathological remodelling in the diabetic heart.